2019
DOI: 10.1017/s146342361900046x
|View full text |Cite
|
Sign up to set email alerts
|

Women’s views on contact with a health visitor during pregnancy: an interview study

Abstract: Aim: To explore recent mothers’ views of the health visiting antenatal contact in England. Background: English health visitors are mandated to be in contact with all women in the third trimester of pregnancy. The aim of this antenatal contact is to assess the needs of the family before the birth and support preparation for parenthood. Recent data show that this contact is provided fragmentarily and not always face-to-face. More information on how women view this contact could inform serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This paper is part of a large programme of work examining the collaboration between healthcare professionals caring for women during and after pregnancy (project website blinded). The data for this paper comes from two qualitative studiesan interview study with midwives and health visitors, and an interview study with postnatal women (findings from the study with postnatal women have previously been published; Olander et al, 2019a;Olander et al, 2019b). The aim of the healthcare professional study was to compare midwives and health visitors' perceived barriers and enablers for working collaboratively during transition of care from midwifery to health visiting services.…”
Section: Methodsmentioning
confidence: 99%
“…This paper is part of a large programme of work examining the collaboration between healthcare professionals caring for women during and after pregnancy (project website blinded). The data for this paper comes from two qualitative studiesan interview study with midwives and health visitors, and an interview study with postnatal women (findings from the study with postnatal women have previously been published; Olander et al, 2019a;Olander et al, 2019b). The aim of the healthcare professional study was to compare midwives and health visitors' perceived barriers and enablers for working collaboratively during transition of care from midwifery to health visiting services.…”
Section: Methodsmentioning
confidence: 99%
“…After searching research databases, the nurse critically appraises the external evidence she has found (EBP level). She learns that nurse-led models of care have been used successfully to provide prenatal care, especially in other countries 22. In the United Kingdom, for example, nurses have provided prenatal and postpartum care to patients in their homes, and this service was perceived by patients as extremely valuable.…”
Section: An Ebpqi Examplementioning
confidence: 99%
“…This is important as a patient's apparent health at the surgery may differ from the reality of their health at home. Olander et al's (2019) paper expresses how home visits are one of the 'triad of core practices' as they form an opportunistic setting for building rapport and uncovering withheld health needs.…”
Section: Development Of Gp's Awarenessmentioning
confidence: 99%
“…Lines of communication with other health professionals and the degree to which information is fed back may go some way in helping to diagnose a new mother with postnatal depression because of the clues that are picked up during this home visit. However, a few participants described how government policy directives have changed the structure of working for health visitors and the impact this has had on interdisciplinary communication and continuity of primary care services for mothers (Derrett and Burke, 2006;Olander et al, 2019). For example, health visitors are no longer allocated to individual practices and instead work collectively and are assigned to wherever there is patient demand with the intention of increasing shared workload and professional support (Cowley et al, 2013;Aquino et al, 2016).…”
Section: Development Of Gp's Awarenessmentioning
confidence: 99%